Absence of interleukin 22 affects the oral microbiota and the progression of induced periapical lesions in murine teeth. (4th April 2014) - de Oliveira, K. M. H.; da Silva, R. A. B.; De Rossi, A.; Fukada, S. Y.; Feres, M.; Nelson‐Filho, P.; da Silva, L. A. B.
Abstract Aim To evaluate the absence of IL‐22 on the progression of periapical lesions in wild‐type (WT) and IL‐22 knockout (IL‐22 KO) mice. Methodology The evaluation of the oral microbial profile of mice was performed by Checkerboard DNA–DNA hybridization from saliva samples. Periapical lesions were induced in manbibular first molars by pulpal exposure and evaluated after 7, 21 and 42 days (n = 15). Haematoxylin‐eosin‐stained sections were analysed under conventional and fluorescence microscopy to evaluate the tissue features and size of periapical lesions and tartrate‐resistant acid phosphatase histoenzymology (TRAP), Brown & Brenn staining and immunohistochemistry. The scores of the number of bacterial cells present in the oral cavity were analysed by the Mann–Whitney test, and the results and comparisons for periapical lesion size and number of osteoclasts were subjected to one‐way anova and Bonferroni's post‐test (α = 0.05). Results Significant differences were observed for bacterial load between the groups of animals for 6 bacterial species (P < 0.05), with five species found in higher levels in the WT group, and one in the IL‐22 KO group. WT mice had significantly larger periapical lesions (P < 0.05) between 7 and 42 days and between 21 and 42 days, with an increase in the mean size and number of osteoclasts. IL‐22 KO mice had an increase in periapical lesion size and number of osteoclasts between 7 and 21 days (P < 0.05). No differences were found between bacteria localization in the root canal system between the experimental groups. Small variations related to the location of immunostaining were found between the groups. Conclusion This study revealed differences in the composition of oral microbiota between mice that may be taken into account in the susceptibility to infections and development of periapical lesions. The absence of IL‐22 in mice resulted in smaller periapical lesions with fewer osteoclasts at the final experimental period, suggesting the participation of IL‐22 in the host immune and inflammatory response to a periradicular infection.